Students' Experience in Facing the TOAFL Test: An Analysis of Learning Strategies, Anxiety, and Motivation in Arabic Learning - Abu Abas; Kuswoyo Kuswoyo (Global Education Journal, 2026)
Arabic language proficiency is a strategic academic competency in Islamic universities, particularly in supporting the understanding of Islamic literature, academic activities, and the development of knowledge. This study aims to analyze students' experiences in taking the Test of Arabic as a Foreign Language (TOAFL), focusing on learning strategies, anxiety, motivation, challenges, and perceptions of the test format. This research method uses a descriptive qualitative approach supported by quantitative data. Data were collected through questionnaires and interviews involving 30 undergraduate students from various semesters who had taken the TOAFL. The results showed that the most effective learning strategy reported by students was regular practice focused on TOAFL question types, particularly the listening and reading sections. Most students experienced anxiety before and during the exam, primarily due to time pressure and question difficulty. However, this anxiety can be reduced through adequate preparation and support from the learning environment. A combination of internal factors, such as personal interest, and external factors, including academic requirements and graduation eligibility, fostered students' learning motivation. The study concluded that the interaction between language proficiency, learning strategies, psychological factors, and learning support systems influenced students' success in the TOAFL.